Perancangan Sistem Informasi Akuntansi Penerimaan Kas Pendaftaran Siswa Baru Menggunakan Visual Studio dan Ms. Acces di SMP Kartika X-I Bandung - Neneng Siti Lutfiah; Karyadi; Rini Suwartika Kusumadiarti (Universitas Sains dan Teknologi Komputer, 2021)
This design aims to determine the cash receipts system for new student registration in order to support the effectiveness of cash receipts for new student registration at SMP KARTIKA XI Bandung. This study uses a qualitative method with a descriptive approach while the software development method uses the water fall method. Data collection techniques using observation, interviews and library studies. Design information system using visual studio and ms.access. Based on the observations made, it turns out that the accounting information system for cash receipts for new student registration is still not perfect. The problems that occur are that the system used is still manual, the reports produced have not been presented quickly and accurately, the files presented are still in the form of hard files. The suggestions that the author gives, it is hoped that the school can manage finances using a good internet network and server. Thus, prospective students can access the software and servers more optimally.